Pengaruh Insentif Finansial Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PDAM Tirta Sukapura Kabupaten Tasikmalaya - Sandy Raharja; Arga Sutrisna; Ghaling Achmad Abdul Ghonisyah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine and analyze the description of financial incentives, work motivation and employee performance of PDAM Tirta Sukapura, Tasikmalaya Regency. The Effect of Financial Incentives and Work Motivation Simultaneously on Employee Performance at PDAM Tirta Sukapura, Tasikmalaya Regency. As well as the Effect of Financial Incentives and Work Motivation partially on employee performance at PDAM Tirta Sukapura, Tasikmalaya Regency. The method used in this study is quantitative descriptive. With a research sample of 67 employees of PDAM Tirta Sukapura, Tasikmalaya Regency as respondents. The data used are primary and secondary data. The analysis tool used in this study is multiple linear regression using the SPSS version 25 support application. The results of the study showed that Financial Incentives for employees of PDAM Tirta Sukapura, Tasikmalaya Regency were qualified with good criteria, for employee work motivation at PDAM Tirta Sukapura, Tasikmalaya Regency it can be said to have good criteria, and for employee performance at PDAM Tirta Sukapura, Tasikmalaya Regency it has high criteria. The results of the hypothesis test show that simultaneously the variables used in the study, namely financial incentives and work motivation, have a significant effect on employee performance at PDAM Tirta Sukapura, Tasikmalaya Regency. Likewise, partially there is a significant effect of financial incentives on employee performance, and partially there is a significant effect between work motivation on employee performance at PDAM Tirta Sukapura, Tasikmalaya Regency.